Reflecting conifer phenology using mobile terrestrial LiDAR: A case study of Pinus sylvestris growing under the Mediterranean climate in Perth, Australia - Lin, Y.; West, Geoff (Elsevier, 2016)
Accurately monitoring of tree phenological dynamics is crucial for understanding how forest ecosystems respond to various climate changes, and a variety of methods recently have been established for accomplishing this task. However, efficient techniques for featuring conifer phenology are still lacking. In fact, characterizing conifer phenological variations have long been an issue, because conifers tend to show hard-to-discern changes in terms of no matter color or crown morphology for different seasons. To address this conventional "conifer issue", this study attempted the state-of-the-art remote sensing technology of mobile terrestrial light detection and ranging (LiDAR) (also termed as mobile terrestrial laser scanning, MLS) to reflect the seasonal-scale phenological variations of conifers, specifically in a case of Scots pines (Pinus sylvestris) growing under the Mediterranean climate in Perth, Australia. The MLS-collected data shows that for the conifers growing under different temperature and precipitation conditions, lasers, in a statistical sense, behave with different penetrations into their crowns. In light of this phenomenon, a new seasonal-scale conifer phenological indicator (CsPI) was proposed, i.e. the ratio between the average of the horizontal penetration distances for the entire laser points backscattered from a crown and its diameter calculated along with the horizontal direction of laser incidence. The performance of the newly-proposed CsPI was assessed by the means of meta-analysis, i.e. comparing the CsPI-indicated conifer response to seasonal climate changes in Perth with the derived rule of stem radial growth rates at different seasons in Mesic, Spain, both in the Mediterranean climate scenarios. The correlations with positive results showed that the proposed schematic plan of applying MLS and the developed phenological indicator both are validated, and this study has opened a new way for reflecting the seasonal-scale phenological variations of conifers.